2022
DOI: 10.1001/jamanetworkopen.2022.41807
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Cognitive Trajectory After Total Joint Arthroplasty

Abstract: ImportanceIndividuals with total joint arthroplasty (TJA) have long-term exposure to metal-containing implants; however, whether long-term exposure to artificial implants is associated with cognitive function is unknown.ObjectiveTo compare long-term cognitive trajectories in individuals with and without TJA.Design, Setting, and ParticipantsThis population-based cohort study assessed serial cognitive evaluations of 5550 participants (≥50 years of age) from the Mayo Clinic Study of Aging between November 1, 2004… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 41 publications
4
10
0
Order By: Relevance
“… Preexisting cognitive impairment (Non-modifiable) - The presence of a cognitive disorder before surgery increases the risk of POCD [ 51 , 52 , 53 ]. Surgical types and techniques (Modifiable) - POCD occurs after major surgeries such as open-heart surgery [ 53 , 54 ], total hip replacement [ 55 , 56 ], carotid surgery [ 57 59 ], and thoracic surgery [ 60 , 61 ]. - In cardiac surgery, off-pump coronary artery bypass grafting (OPAC) is associated with a reduced risk of POCD and is linked to cognitive improvement after cardiac surgery [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Preexisting cognitive impairment (Non-modifiable) - The presence of a cognitive disorder before surgery increases the risk of POCD [ 51 , 52 , 53 ]. Surgical types and techniques (Modifiable) - POCD occurs after major surgeries such as open-heart surgery [ 53 , 54 ], total hip replacement [ 55 , 56 ], carotid surgery [ 57 59 ], and thoracic surgery [ 60 , 61 ]. - In cardiac surgery, off-pump coronary artery bypass grafting (OPAC) is associated with a reduced risk of POCD and is linked to cognitive improvement after cardiac surgery [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…- POCD occurs after major surgeries such as open-heart surgery [ 53 , 54 ], total hip replacement [ 55 , 56 ], carotid surgery [ 57 59 ], and thoracic surgery [ 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…All models were adjusted for age at current visit, age 2 at current visit, education level (in years), practice effects, and sex. Previous studies have shown there is typically a substantial practice effect from the first to second visit as well as smaller practice effects after the second visit 36–39 . Therefore, we account for practice effects by a term for difference between visit 1 and subsequent visits (not visit 1 vs. visit 1) as well as terms for time (years) since visit 1 and time (years) since visit 1 squared 39 .…”
Section: Methodsmentioning
confidence: 99%
“…Psychometric properties: Psychometric properties of component measures and composites were examined descriptively shown there is typically a substantial practice effect from the first to second visit as well as smaller practice effects after the second visit [36][37][38][39] . Therefore, we account for practice effects by a term for difference between visit 1 and subsequent visits (not visit 1 vs. visit 1) as well as terms for time (years) since visit 1 and time (years) since visit 1 squared 39 . Between subject variability was accounted for by ran-…”
Section: Methodsmentioning
confidence: 99%
“…These authors, based in Rochester (Minnesota, USA) , set out to establish what happens to a patient’s cognitive ability following total joint arthroplasty (TJA). 3 They attempted to answer the question by assessing serial cognitive evaluations of 5,550 participants (aged 50 years and older) from the Mayo Clinic Study of Aging, to assess the effect of TJA on cognitive trajectory in patients following surgery. The authors found no difference in the observed rate of cognitive decline in those with or without TJA until age 80 years, after which there was a slightly faster cognitive decline that was also found in those more than eight years from surgery.…”
Section: Long-term Cognitive Trajectory After Total Joint Arthroplastymentioning
confidence: 99%